Gaya Hidup yang Berhubungan dengan Kejadian Kegemukan pada Remaja Putri di Kota Tasikmalaya, Jawa Barat, Indonesia : Gaya Hidup yang Berhubungan dengan Kejadian Kegemukan pada Remaja Putri di Kota Tasikmalaya, Jawa Barat, Indonesia - Hidayanti, Lilik; Saraswati, Dian; Aisyah, Iseu Siti (Amerta Nutrition, 2023)
Background: Adolescence, specifically among female is a high-risk period for weight gain and the incidence of being overweight. Lifestyle is considered a significant contributing factor to overweight in female adolescents. Objectives: This study aimed to examine the association between lifestyle, particularly daily activity and eating habits with the incidence of being overweight among female adolescents in Tasikmalaya City, West Java. Methods: A cross-sectional design was used with 275 subjects from seven state junior high schools selected by proportional random sampling. The data collected included demographics, lifestyle comprising daily activity, eating habits, as well as the incidence of being overweight, measured using the Body Mass Index-Age-Z score (BAZ). The association between lifestyle and overweight was evaluated using binary logistic regression. Results: The results showed that out of 275 subjects, 51 were overweight (18.5%) and 224 (81.5%) had normal weight. The risk factors for being overweight included sleeping less than seven hours a day (p=0.017; OR=3.020; 95%CI=1.218-7.486), mild physical activity (p=0.008; OR=19.251; 95%CI=2.170-170.790), breakfast frequency less than 3 times a week (p=0.033; OR=2.418; 95% CI=1.074-5.443) and frequent snacking habits (p=0.000; OR=15.022; 95% CI=5.922-43.846). Conclusions: Several lifestyles were found to significantly impact the incidence of being overweight among female adolescents, thus  suggesting the need to make lifestyle  modifications.